X-ray test on passion fruit seeds submitted to different aryl removal methods - Severiano, Rogerio Luciano; Pinheiro, Paloma Rayane; Gomes Junior, Francisco Guilhien; Medeiros, Andre Dantas de; PEREIRA, MARCIO DIAS (Comunicata Scientiae, 2018)
Passion fruit seeds present germination problems which are mainly attributed to growth regulating substances present in aryl. The objective of this work was to evaluate the quality of passion fruit seeds submitted to different aryl removal methods by the X-ray test compared to the traditional viability and vigor tests. Seeds extracted from giant yellow passion fruit were purchased from a local market and then subjected to the following aryl removal techniques: water degumming, sand rubbing, mechanical blending, fermentation and virgin lime. After aryl removal, the seeds were submitted to a physiological quality evaluation by the moisture degree, germination, first germination count, germination speed, and seedling length, and also a physical quality evaluation by X-ray test. The treatments using fermentation and virgin lime were harmful to the seeds and the aryl removal techniques of passion fruit seeds by means of degumming in water, sand friction and mechanically with a blender presented the best results. The X-ray test was efficient in identifying mechanical damage and deformations in passion fruit seeds.